Clastic cells are absent around the root surface in pulp‐exposed periapical periodontitis lesions in mice. (26th February 2018) - Shah, A; Lee, D; Song, M; Kim, S; Kang, MK; Kim, RH
Abstract: Introduction: Clastic cells, originating from the monocyte–macrophage lineage, resorb mineralized tissues. In periapical periodontitis, alveolar bone around the tooth apex becomes resorbed; however, the roots of the teeth are often left intact by yet unknown mechanisms. Here, we examined the status of clastic cells in a periapical periodontitis model in mice. Methods: Periapical periodontitis was induced by performing pulp exposure on the maxillary first molar. The contralateral maxillary first molar was used as a control. The maxillae were harvested, fixed, and subjected to μCT scanning and three‐dimensional volumetric analysis. TRAP staining was performed, and osteoclasts were quantified. Immunohistochemical staining was performed for RANKL, OPG, and F4/80, a marker for macrophages. Results: At the apex of the tooth, pulp exposure resulted in periapical radiolucency with mineralized tissues at the surrounding bone surfaces but not on the root surfaces. Histologically, clastic cells were present on the bone surfaces but absent around the root surfaces. Expression of F4/80 and RANKL was not found at close proximity to the root surfaces, but OPG was globally expressed. Conclusion: The absence of clastic cells around the root surface of pulp‐exposed teeth, in part, is associated with the lack of macrophages and RANKL expression.